Incidence and transmiáion of Faba bean necrotic yellows virus (FBNYV) in Spain - Ortiz, V.=700 1 Navarro, E.; Castro, s.; Carazo, G.; Romero, J.
(Es, En)
ilus., 32 ref.
Keywords: LEGUMINOSAS; VIRUS; INFECCION; APHIDIDAE; ESPAÑA; ELISA-TAS; IC-PCR; INFECCIONES; MIXTAS; PULGONES VIRULIFEROS; SECUENCIACION; VIRUS DE LEGUMINOSAS; VIRUS DEL AMARILLENTO NECROTICO DEL HABA